Digital Copywriting Strategy: A Pillar of Increasing the Competitiveness of MSMEs in The Midst of Market Competition - Nur Rahmadina; Alex Kisanjani; Marulan Andivas; Dimaz Harits (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The increasingly fierce market competition, especially in the batik industry, requires MSMEs to have a strong differentiation strategy and product branding. The goal is to maintain and improve the competitiveness of the product in the market. Unfortunately, Zahro Batik MSMEs still face obstacles, where digital promotion efforts still tend to be simple, use social media captions that are less informative, have minimal appeal, and are not optimal in reaching potential consumers. This condition is caused by the limitation of copywriting skills which are the key to digital marketing. The purpose of this service activity is to improve the understanding and skills of business actors in optimizing marketing communication strategies through the preparation of effective and attractive promotional messages. The method used is socialization and copywriting training. This activity was attended by 15 participants who are employees of Batik Zahro MSMEs and local residents as an expansion of partners. Evaluation was carried out through individual assignments in the form of writing product promotional captions, which were assessed based on the suitability of the content, language appeal, and creativity of the message. The results achieved showed an increase in participants' soft skills and understanding, where all participants were able to compile promotional captions in a structured manner using the copywriting techniques that had been taught. This increase is expected to strengthen the brand image and product attractiveness, as well as encourage the readiness of Zahro Batik MSMEs to compete and develop in the creative industry.